PATTERN OF PSYCHIATRIC REFERRAL FROM EMERGENCY DEPARTMENT OF A TERTIARY LEVEL HOSPITAL IN NEPAL - Ranjan, Sanjeev; Poudel, Reet; Pandey, Pradeep (Journal of Universal College of Medical Sciences, 2016)
INTRODUCTION: Emergency department serves as one of the gateway through which patients with psychiatric disorders come for treatment. The referral to the psychiatry department enables a psychiatrist to provide services to these patients in need. So, the study of this pathway of care becomes important. MATERIAL AND METHODS: A total of 100 consecutive patients referred from emergency to the department of psychiatry were enrolled in this study. Their socio-demographic variables, reason and purpose for referral was assessed. The psychiatric diagnosis was made according to the International Classification of Diseases -10 (ICD-10) system. RESULTS: The psychiatric referral rate from the emergency was found to be 8.46%. Out of one hundred patients more referred patients were female (64%), from rural background (90%). Family members were the source of referral for emergency visit in most of the patients (74%). Dissociative disorder was the most common diagnosis (26%) followed by acute & transient psychotic disorders at 12%. CONCLUSIONS: Fewer patients are referred to psychiatry department even in a tertiary level hospital of Nepal. Journal of Universal College of Medical Sciences (2015) Vol.03 No.02 Issue 10 Page : 5-9